DYNAMICS OF APPLICATION OF SALUS POPULI SUPREMA LEX ESTO IN LAW ENFORCEMENT IN INDONESIA - Orien Effendi; Ro'is Alfauzi (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2021)
This paper analyzes the position and legality of the use of principles outside the legal text (unwritten) as the basis for law enforcement in Indonesia. As is known, the sources of law include laws, customs, jurisprudence, and doctrine. So whether the presence of legal provisions outside of legal sources can be used as the basis for law enforcement. This analysis highlights the public assumption that the use of the principle of